Examining High School Students’ Cognitive Structures on the Concept of Cleaning Agent through Word Association Test - Alkan, Fatma; Dinçdemir, Dilay; Yücel, Ayşem Seda (Jurnal Penelitian dan Pembelajaran IPA, 2021)
The aim of this research is to determine high school students’ cognitive structure regarding cleaning agent via word association test. The sample of the research consists of 160 high school students. A word association test (WAT) prepared to test the structure addressed in the study was used as the data collection tool. Content analysis was used to evaluate the data obtained from the sample group. Words written by high school students in relation to the test were analyzed elaborately and based on this analysis concepts were categorized as well as their frequency. As for the first section of the word association test, three main categories were obtained: Chemical cleaning agent, natural cleaning agent, and cleaning equipment. When it comes to the second part, the highest frequency values were in the category of chemical cleaning agent, natural cleaning agent category, cleaning equipment category. All in all, it was concluded that the natural cleaning agent category had the highest frequency, the chemical cleaning agent category was in the second place, and the cleaning equipment category had the lowest frequency.